Quality of pre-service teachers’ reflections – a mixed-method study - Zhang, Chengming; Schießl, Jessica; Plößl, Lea; Hofmann, Florian; Gläser-Zikuda, Michaela (Reflexion in der Lehrkräftebildung: empirisch - phasenübergreifend - interdisziplinär, 2022)
In teacher education, reflection is seen as a crucial aspect of professionalization (Hatton & Smith, 1995) and may be supported by using a portfolio (Gläser-Zikuda, Feder, & Hofmann, 2020). To analyze reflective writing and the quality of reflection ,in recent years, researchers on the one hand use qualitative analyses (Fütterer, 2019), on the other hand automated and multi-dimensional approaches became relevant (Kovanović et al., 2018;Ullmann, 2019). Therefore, the aim of the study (funded by the BMBF) is (a) to analyze the quality of reflection using different research methods, (b) to explore the relation between linguistic features of reflective writing and the quality of reflection, and (c) to identify gender differences in linguistic features and quality of reflection. N = 709 pre-service students wrote reflections using an e-portfolio related to specific educational tasks. For the analysis, we applied a structured qualitative content analysis (Gläser-Zikuda,Hagenauer, & Stephan,2020) and computerlinguistic analyses (Pennebaker et al.,2015) to analyze the quality of reflection (Fleck & Fitzpatrick,2010) in n = 100 texts randomly selected out of 506 texts. The results of the content analysis indicate that the hierarchy of pre-service teachers’ reflections was distributed at the low and middle levels (Description = 20, Reflective Description = 61, and Dialogic Reflection = 17), while reflections at the high level (Transformative Reflection and Critical Reflection) were not. Second, the linguistic features collected using LIWC were not statistically different in morphology, syntax, and semantics at different levels of reflection. Nevertheless, the linguistic features at the morphology level were significant in the reflective writing by gender.<br
Keywords: Teacher Education; Quality of Reflection; E-Portfolio; Mixed-Methods; Linguistic Features